Effect of parent's education on children's time use: Evidence from Spain - Caparrós-Ruiz, Antonio (My University, 2014)
Children's time use is of great interest for both parents and policy makers. The concern is because allocation of time by the young people between productive and unproductive activities, their social patterns and their habits of active and passive leisure shape their personality and have important long-term consequences on their academic and employment success. Many economic studies have reported on how the family environment affects how young people spend their time. The household type, the parents’ characteristics and family customs are related with the way in which young people spend their time. An interesting issue in this context is how the parental education affects the time-use patterns of children. The time use's patterns associated with the human capital acquired by the parents along with their relations with the family’s socioeconomic status, the social networks and the access to information constitute alternative scenarios that determine the activities of young people throughout the day and have an economic impact in the future. The main objective of this paper is to analyse these topics for Spain, paying special attention to the effects of parents’ education on children’s time use. The empirical analysis use data from Time Use Survey (INE). This dataset is suited for the purpose of this study since it uses a statistical measure called “time budget” that records the sequence and duration of activities conducted by a person over a period of 24 h, and provides information about the personal characteristics of the household members. The specification and estimation of censored regression models will be the methodology applied.
Keywords: Niños - Educación; Human capital; Time use; Children